DEVELOPMENT OF CONCEPT-BASED LEARNING METHODS THROUGH DIGITAL GAMES - Utami, Irma Inesia Sri; Muhdiyati, Iyon; Akhmad, Syarif; Silpiani, Hopipah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is based on the problem of students' low understanding of concepts in social studies subjects. The challenges of the digital era underlie updates in the technical teaching of concepts that utilize technology. The need for product development innovation to bridge the problem of low understanding of concepts and the demands of the digital era encourages development research to produce products through concept-based learning methods through digital games. This research aims to create a product in the form of a concept-based learning method designed through digital games in social studies subjects suitable for use. The research method used is research and development with the ADDIE (Analysis, Design, Development, Implementation & Evaluation) model. Data collection techniques use observation, interviews, and questionnaires. This research involves expert judgment for learning method experts and learning design. The data analysis technique uses quantitative descriptive. The research results show that the concept-based learning method through digital games is declared feasibility. Based on validation, learning method experts obtained a percentage of 82.5%, while learning design experts obtained 80%. The results of the limited trial obtained a percentage of 92% stating that the product was worthy of being tested at the next level and the results obtained were 93% of respondents stating that the product was considered feasible. Based on this, it can be concluded that the concept-based learning method through digital games in this research is declared to meet the feasibility. The research results show the novelty of product development in a syntax designed to be oriented towards concept development in digital game design with schemes of team sharing. The researcher recommends that future researchers develop more diverse concept learning in digital games.